A Matter of Perspective? Disentangling the Emic-Etic Debate in the Scientific Study of Religion\s - Mostowlansky, Till; Rota, Andrea 1983- (2016)
This article introduces the emic–etic debate in the scientific study of religion\s and provides a frame for the special issue’s six articles on the topic. Departing from the broader debate’s early history in the 1960s, this article contextualizes the emic–etic debate and locates its point of entry into the scientific study of religion\s in the 1980s. This article argues that in the course of the debate the insider–outsider and emic–etic complexes have become entangled. In order to facilitate an understanding of the debate, this article maintains that the emic–etic debate in the scientific study of religion\s touches upon three central dimensions (existential–political, methodological, and epistemological). In order to move toward a clearer methodological and epistemological framework, this article furthermore proposes an iterative model that locates insider–outsider at the level of observers and emic–etic at the level of categories.
Keywords: emic–etic -- insider–outsider -- methodology -- epistemology -- Pike -- Harris -- McCutcheon